Electroencephalographic characteristics of children and adolescents with chronic musculoskeletal pain. (22nd November 2022) - Ocay, Don Daniel; Teel, Elizabeth F.; Luo, Owen D.; Savignac, Chloé; Mahdid, Yacine; Blain-Moraes, Stefanie; Ferland, Catherine E.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Introduction: The pathophysiology of pediatric musculoskeletal (MSK) pain is unclear, contributing to persistent challenges to its management. Objectives: This study hypothesizes that children and adolescents with chronic MSK pain (CPs) will show differences in electroencephalography (EEG) features at rest and during thermal pain modalities when compared with age-matched controls. Methods: One hundred forty-two CP patients and 45 age-matched healthy controls (HCs) underwent a standardized thermal tonic heat and cold stimulations, while a 21-electrode headset collected EEG data. Cohorts were compared with respect to their EEG features of spectral power, peak frequency, permutation entropy, weight phase-lag index, directed phase-lag index, and node degree at 4 frequency bands, namely, delta (1–4 Hz), theta (4–8 Hz), alpha (8–13 Hz), and beta (13–30 Hz), at rest and during the thermal conditions. Results: At rest, CPs showed increased global delta ( P = 0.0493) and beta ( P = 0.0002) power in comparison with HCs. These findings provide further impetus for the investigation and prevention of long-lasting developmental sequalae of early life chronic pain processes. Although no cohort differences in pain intensity scores were found during the thermal pain modalities, CPs and HCs showed significant difference in changes in EEG spectral power, peak frequency, permutation entropy, and network functional connectivity at specific frequency bands ( P < 0.05) during the tonic heat and cold stimulations. Conclusion: This suggests that EEG can characterize subtle differences in heat and cold pain sensitivity in CPs. The complementation of EEG and evoked pain in the clinical assessment of pediatric chronic MSK pain can better detect underlying pain mechanisms and changes in pain sensitivity.